Detachment of Extensor Carpi Ulnaris and Anterior Branches of the Radial Collateral Ligament from the Epicondyle: A Modification of Kocher Lateral Approach for the Treatment of Radial Head Fractures - Touloupakis, Georgios; Biancardi, Elena; Ghirardelli, Stefano; Antonini, Guido; Crippa, Cornelio (Joints, 2019)
Purpose The aim of this study is to present clinical results of a retrospective case series that includes patients treated with an extensive modification of the Kocher lateral approach to the elbow with surgical detachment of the anterior branches of the radial collateral ligament.Methods From January 2016 to January 2018, nine patients with closed isolated displaced or multifragmentary radial head fractures (Mason type II, III, or IV) who underwent osteosynthesis or arthroplasty through a modified Kocher lateral elbow approach were available for follow-up.Results There were six female and three male patients. The median age at the time of surgery was 52 years old (range: 26–70). The dominant upper limb was injured in 22.2% of patients. After a median follow-up of 8 (range: 6–27) months, all patients regained completely all their daily activities and no cases of infections were recorded.Conclusion We believe that the approach proposed can be a useful choice to deal with these challenging injuries. Our strategy may represent a valid alternative to more popular approaches as the use of anchors decreases the risk of instability that is the major danger considered in the past when soft tissues as tendons and ligaments are detached.Level of Evidence This is a level IV study (therapeutic case series).
Keywords: radial head fractures; lateral approach to the elbow; lateral collateral ligament; radial collateral ligament